Development of a new airlift-driven raceway reactor for algal cultivation - Ketheesan, B.; Nirmalakhandan, N. (Elsevier, 2010)
This paper presents the development and analysis of a new airlift-driven raceway reactor configuration for energy-efficient algal cultivation. A theoretical analysis of the energy requirements for traditional paddlewheel-driven raceway reactors and the proposed airlift-driven raceway reactors is presented. A hydrodynamic model was developed to predict the liquid circulation velocity in the reactor system based on theoretical energy balance. The predicted liquid velocity agreed well with experimentally measured liquid velocity with r2 = 0.89. Based on the results of this analysis, the energy required for maintaining typical raceway velocity of 14 cm/s for mixing and keeping the cultures in suspension in a paddlewheel- driven raceway could be reduced by as much as 80% with the proposed configuration. Growth of Scenedesmus sp. was evaluated in a laboratory scale, 20 L version of the proposed reactor configuration using artificial lighting under ambient temperatures without any supplementary carbon dioxide sparging. The volumetric algal biomass productivity achieved in the proposed configuration (0.16 ± 0.03 dry g/L day) is comparable or better than that reported in the literature for paddlewheeldriven raceways.
Keywords: Microalgal cultivation; Paddlewheel-driven raceway reactor